"Unpacking state-society relations in the urban space: What are the Limit(s) of compromise?". The dilemma about answering such a question and some recent Venetian experiences. (June 2023) - Cristiano, Silvio
Confronted by answering a complex question such as 'What are the Limit(s) of Compromise?' when 'unpacking State-Society Relations in the Urban Space', some problematising thoughts are offered to further elaborate urban studies by resorting to systems thinking and its leverage points concept. Both social and ecological issues are addressed, and specific references to Venice, Italy, are offered, including recent grassroot experiences. The dissertation includes some epistemological dilemmas and some initial projections to start to measure ourselves with a new epoch, able to interact with all of the above: social, ecological, urban, and power/governance dimensions.